A case study on professional skills and accredited graduate programs of marketing - Silvana Dakduk; María del Pilar García-Chitiva; Juan C. Correa (Applied Network Science)
Abstract We model the relationship between professional skills and higher education programs as a non-directed bipartite network with binary entries representing the links between 28 skills (as captured by the occupational information network, O*NET) and 258 graduate program summaries (as captured by commercial brochures of graduate programs in marketing with accreditation standards of the “Association to Advance Collegiate Schools of Business”). While descriptive analysis for skills suggests a qualitative lack of alignment between the job demands captured by O*NET, inferential analyses based on exponential random graph model estimates show that skills’ popularity and homophily coexist with a systematic yet weak alignment to job demands for marketing managers.